2022
DOI: 10.1212/wnl.0000000000200021
|View full text |Cite
|
Sign up to set email alerts
|

Neurofilament Light Chain Levels in Anti-NMDAR Encephalitis and Primary Psychiatric Psychosis

Abstract: Introduction:An important challenge in diagnosing anti-NMDAR encephalitis (NMDARe) is differentiating it from a first episode of psychosis (FEP) caused by a psychiatric disease (pFEP). CSF antibody testing distinguishes these diseases, but spinal taps are difficult to obtain in psychiatric facilities. A separate problem is the lack of biomarkers of NMDARe severity and outcome. Here we assessed the performance of neurofilament light chain (NfL) testing in these settings.Methods:In this observational study, NfL … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
38
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(41 citation statements)
references
References 41 publications
3
38
0
Order By: Relevance
“…Kammeyer et al (117) collected 26 plasma and 14 CSF samples of patients with autoimmune neurological disorders, compared to the control group, and patients with active AE show an elevated level of plasma Nfl, implying that it may act as a minimally-invasive biomarker for CNS injury during AE development. Another study also confirmed the opinion that the Nfl level is closely related to disease severity during diagnosis (118).…”
Section: Neurofilament Light (Nfl)supporting
confidence: 64%
“…Kammeyer et al (117) collected 26 plasma and 14 CSF samples of patients with autoimmune neurological disorders, compared to the control group, and patients with active AE show an elevated level of plasma Nfl, implying that it may act as a minimally-invasive biomarker for CNS injury during AE development. Another study also confirmed the opinion that the Nfl level is closely related to disease severity during diagnosis (118).…”
Section: Neurofilament Light (Nfl)supporting
confidence: 64%
“…2 ). It seems relevant if neurodegeneration markers such as neurofilament light chains are elevated and exceed 15 pg/ml in patients experiencing their first psychotic episode, if those patients develop NMDARE [ 41 ]. Another issue seems to be the presence of CSF-NMDAR antibodies, as such CSF-NMDAR autoantibodies are associated with a higher percentage of patients suffering from psychiatric symptoms [ 42 ].…”
Section: Pathogenic Role Of Nmdar Antibodies In Psychiatric Disordersmentioning
confidence: 99%
“…In such cases other tools might help identify patients with a potential NMDAR-antibody associated encephalitis, like quantitative EEGs with a fast-slow ratio index as a very sensitive early sign of NMDAR encephalitis [ 49 ]. There are other markers of neuronal damage in the same context that might help identify first-episode psychosis patients with NMDAR antibodies as neurofilament light chains is a particular marker of disease severity in first-episode psychosis, but not a long-term disease marker, as a recent study by Guasp et al [ 41 ] showed. Old and novel biomarkers could thus help us interrupt the autoimmune continuum of NMDAR pathogenicity from psychiatric diseases associated with NMDAR autoantibodies and NMDARE ( Fig.…”
Section: Pathogenic Role Of Nmdar Antibodies In Psychiatric Disordersmentioning
confidence: 99%
“…Given the current lack of availability of lumbar puncture facilities in most mental healthcare settings, further research using prospective methods is urgently needed to investigate the feasibility of developing a clinical tool that captures the complex psychopathology associated with NMDAR-antibody mediated disorders. In addition, alternative biomarkers that do not require CSF sampling, such as neurofilament light chain, may have clinical utility in identifying patients with NMDARE[ 13 ]. Such approaches would help clinicians identify which patients are in greatest need of CSF antibody testing [ 1 ].…”
Section: Discussionmentioning
confidence: 99%